Hubungan Karakteristik Topografi dengan Sifat-Sifat Fisika Tanah Studi Kasus: Sub DAS Citarik, DAS Citarum Hulu - Ade Setiawan; Mahfud Arifin; Rachmat Harryanto; Apong Sandrawati (Fakultas Pertanian Universitas Padjadjaran, 2018)
The proper understanding about spatial soil diversity is very important to simulate environmental model and to manage land resources in the landscape scale. Information of soil diversity is also noteworthy for environmental academics, forestry, civil engineering, and land use planner. Until now, most of the soil information are derived from conventional soil maps which are lack of detailed information. This condition can increase the uncertainty of model output and can also be an obstacle to the future development of spatial distribution model. According to this situation, the research was conducted in Sub Watershed of Cikeruh, Citarik, and Citarum Hulu. These areas are located in the 6o53’00”S - 6o53’15” S and 107o45’21”E - 107o45’55”E at 780-1800 m asl, The rainfall is classified as type C according to the Schmidt and Fergusson classification with mean rainfall around 1795.66 mm per year. The soils in the research areas are classified as Inceptisols. The research aims to analyze and elucidate the relation between topographic characteristics and soil physical properties. Some parameters studied in this research are elevation, aspect, plan curvature, profile curvature, topographic wetness index (TWI), topographic position index (TPI), and some soil physical properties, such as soil texture (clay, silt, and sand), soil organic carbon, soil bulk density, soil available water capacity, soil porosity and permeability. The results showed that all topographic parameters were related to one or some soil physical properties, except aspect and slope. Topographic variables that are frequently related to soil properties are TPI and TWI. Keywords: topographic characteristics, elevation, aspect, curvature, TWI, TPI, soil physical properties